Determinants of acute malnutrition among 6–59 months old children in public hospitals in Gambella town, Southwest Ethiopia: unmatched case-control study - Gesese, Abreha Addis; Khot, Luel Duoth (Frontiers in Nutrition, 2023)
Background Acute malnutrition is a severe public health issue caused by poor nutrition over a short period of time. It is a powerful predictor of mortality. The Gambella region’s risk factors for acute malnutrition, however, are not well understood. Thus, the risk factors for acute malnutrition were identified in this study. Methods A facility-based unmatched-case control study design was conducted in public hospitals in Gambella town from February 15 to March 30, 2019. A total of 85 cases and 170 controls were included in the study. According to the average monthly caseload, children between the ages of 6 and 59 months were distributed among the public hospitals. Then, cases and controls were chosen using a systematic random sampling technique. A standardized, previously tested questionnaire was used to collect the data. EPI-data version 3.1 was used to enter the data, which was subsequently exported to SPSS version 20 for analysis. Statistical significance was set at p 0.05 for the bivariate and multivariable logistic regressions that were employed. Results Household income of <=1,500 birr [AOR = 2.46 at 95% CI (1.37–4.39)], being unemployed [AOR = 2.37 at 95% CI (1.34–4.20)], rural residence [AOR = 1.96 at 95% CI (1.10–3.51)], having diarrhea [AOR = 2.47, 95% CI (1.36–4.51)], fever [AOR = 2.05, 95% CI (1.03–4.10)], and pneumonia (AOR = 2.41), and exclusive breast feeding (AOR = 1.96, and exclusive breast feeding [AOR = 1.96, 95% CI (1.18–4.91)], and exclusive breast feeding (AOR = 1.96) minimum dietary diversity [AOR = 2.86, 95% CI (1.06–3.64)], minimum dietary diversity [AOR = 2.86, 95% CI (1.37–5.95)], weight measurement at birth [AOR = 0.86, 95% CI (0.08–0.93)], unplanned birth of the child [AOR = 1.97, 95% CI (1.02–3.78)], and non-immunized [AOR = 4.12, 95% CI (1.05–16.13)] were associated with acute malnutrition. Conclusion This research identified multiple risk factors for acute malnutrition in children aged 6–59 months, suggesting health interventions, and programs at all levels of the system executed in an organized manner with substantial program ramifications.